Development and Characterization of Composite Flour from Sprouted Wheat and Cardaba Banana for Food Applications - Racheal Babalola; Williams Addejuwon; Roseline Adebayo; Olubunmi Akindele; James Oyedokun; Oluwadamilola Ogunsade; Oluseye Abiona; Oluwatosin Ponnle (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2026)
Demand for instant foods without health implications have caused a paradigm shift from the basic raw material (wheat grains) to composite flour. However, compositing does not provide some of the nutritional values desired by food processors, which has led to the need for alternative means of improving the nutritional value of flour for instant foods. The study explored the functional and pasting properties of sprouted wheat grains and cardaba banana flour. The WAC (186.51 to 262.38%), bulk density (0.44 to 0.64%), OAC (204.46 to 285.26%), foam capacity (102.68 to 120.92%), foam stability (62.30 to 89.45%), emulsion capacity (0.39 to 0.45%), and emulsion stability (35.74 to 54.64%) were determined. Results for pasting properties showed the peak viscosity (274.50 to 5750.50 RVU), trough viscosity (173.00 to 3684.00 RVU), breakdown viscosity (103.00 to 2066.50 RVU), final viscosity (281.00 to 6191.50 RVU), and setback viscosity (110.00 to 2507.50 RVU), peak time (4.73 to 5.24 minutes), and pasting temperature (0.00 to 85.95 ). The results obtained based on the pasting and functional composition showed that the sample's nutritional assessment was good; however, sample C (90 SWF: 10 CBF) had the best sample formulation based on the assessed nutritional properties.